Cationic Iron Half-Sandwich Complexes of Aminopyridines: Synthesis and Characterisation - Michieka, Kingsley; Changamu, Evans; Chengo, Katana (Asian Journal of Chemistry, 2025)
The reaction of [(η5-C5H5)Fe(CO)2]+, with the aminopyridine ligands lead to formation of cationic organometallic complexes of the general formula [(η5-C5H5)Fe(CO)2L]+ (where L = 2-Apy, 3-Apy, 4-Apy and Apy = aminopyridine). These ligands have the ability to coordinate to a metal center in monodentate fashion via the pyridine ring or amine nitrogen atoms, can form chelate complexes with one metal center or bridge two metal ions. Spectroscopic data (FTIR, 1H and 13C NMR and elemental analysis) collected for the five metal complexes is consistent with monodenate coordination mode through the pyridyl nitrogen in complexes 2, 3 and 4 atoms and amine nitrogen in complexes 1 and 4.